Determining the anti-cancer properties of Zinc and Novel quinoxaline derivatives on lung cancer cells - Sibiya, Mixo Aunny (My University, 2020)
Despite major advancements in the development of various chemotherapuetic agents, treatment for lung cancer remains costly, ineffective, toxic to neighbouring normal noncancerous cells and still hampered by high level of remissions (Wistuba et al., 2018; Tana et al., 2016; Schiller et al., 2002). Synthesis of novel quinoxalines with a wide spectrum of biological activities has recently received considerable attention with promising anticancer drug activity since most of them do not affect non-cancerous cells and are derived from readily available less costly raw materials (Srivastava et al., 2014). Since combination treatment has been shown to augment and improve single drug treatment, trace elements were employed in this study in combination with quinoxalines derivatives (Gomez et al., 2016; Kocdor et al., 2015; Ku et al., 2012; John et al., 2010; Killile and Killilea, 2007). Zinc is an essential element that is integral to many proteins and transcription factors which regulate key cellular functions such as the response to oxidative stress, DNA replication, DNA damage repair, cell cycle progression, and apoptosis (Dhawan and Chadha, 2010). Owing to the importance of these two approaches, the aim of this study was to provide in vitro preliminary anticancer activity data on A549 lung cancer cells using combination of zinc and quinoxaline derivatives. An assessment of the quinoxaline derivatives ferric reducing power and DPPH free radical scavenging activity was performed. The cytotoxic and anti-proliferation activity of these derivatives and zinc on cancer cell lines was determined using the MTT assay. The ability of the quinoxaline derivatives and zinc to modulate oxidative stress was evaluated using the H2DCFDA fluorescence assay. Cell cycle arrest stages were analysed by flow cytometry through propidium iodide cell cycle analyses. The ability of the quinoxaline derivatives to induce apoptosis in cancer cells was assessed using DAPI/PI, Acridine Orange/Ethidium Bromide (AO/EB) and Annexin V-FITC/Dead Cell assays. Western blot was used to investigate the Bcl/Bax expression ratios in A549 lung cancer cells after treatment with quinoxaline derivatives, zinc and in combination. Of the four quinoxaline derivatives tested, 3-(quinoxaline-3-yl) prop-2-ynyl methanosulphate (LA-39B) and 3-(quinoxaline-3-yl) prop-2-yn-1-ol (LA-55) produced significant anticancer properties against A549 lung cancer cells at minimal concentrations of 25μM. Both quinoxaline derivatives displayed antioxidant properties and did not induce cell death in non-cancerous Raw 267.4 macrophage cells. Cytotoxicity was observed in A549 lung cancer, HeLa cervical cancer and MCF-7 breast cancer cells albeit inhibition was more pronounced in A549 lung cancer cells. Treatment of cancer cells with zinc also resulted in pronounced cytotoxicity at a minimal concentration of 25μM. Although reduced oxidative stress was observed in Raw 264.7 macrophages, in A549 lung cancer cells both compounds were able to increase ROS production which was accompanied by high levels of apoptosis when treated with derivatives and zinc alone but when in combination an improved higher level of apoptosis is observed. The improved anti-cancer activity of this drug combination treatment was further accompanied by lower Bcl/Bax expression ratios with upregulation of Bax in A549 lung cancer cells. The results of the study suggest that 3-(quinoxaline-3-yl) prop-2-ynyl methanosulphate and 3-(quinoxaline-3-yl) prop- 2-yn-1-ol are potential candidates drug for treatment of lung cancer. The use of these quinoxaline derivatives in combination with zinc can offer alternative treatment options for lung cancer.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2020
Keywords: Lungs -- Cancer -- Chemotherapy; Cancer cells -- Adaptation